Characterizing the spatial signal of environmental DNA in river systems using a community ecology approach. (17th November 2021) - Cantera, Isabel; Decotte, Jean‐Baptiste; Dejean, Tony; Murienne, Jérôme; Vigouroux, Régis; Valentini, Alice; Brosse, Sébastien
Abstract: Environmental DNA (eDNA) is gaining a growing popularity among scientists but its applicability to biodiversity research and management remains limited in river systems by the lack of knowledge about the spatial extent of the downstream transport of eDNA. Here, we assessed the ability of eDNA inventories to retrieve spatial patterns of fish assemblages along two large and species‐rich Neotropical rivers. We first examined overall community variation with distance through the distance decay of similarity and compared this pattern to capture‐based samples. We then considered previous knowledge on individual species distributions, and compared it to the eDNA inventories for a set of 53 species. eDNA collected from 28 sites in the Maroni and 25 sites in the Oyapock rivers permitted to retrieve a decline of species similarity with increasing distance between sites. The distance decay of similarity derived from eDNA was similar and even more pronounced than that obtained with capture‐based methods (gill‐nets). In addition, the species upstream‐downstream distribution range derived from eDNA matched to the known distribution of most species. Our results demonstrate that environmental DNA does not represent an integrative measure of biodiversity across the whole upstream river basin but provides a relevant picture of local fish assemblages. Importantly, the spatial signal gathered from eDNA was therefore comparable to that gathered with local capture‐based methods, which describes fish fauna over a few hundred metres.